Experiences of women with breast cancer undergoing chemotherapy: A study at Ho Teaching Hospital, Ghana - Senam Kudjawu; Joana Agyeman‐Yeboah (Wiley, 2021)
Abstract Aim The study explored the experiences of women with breast cancer undergoing chemotherapy at Ho Teaching Hospital. Design A qualitative design which was exploratory and descriptive in nature was employed. Methods Purposive sampling was used to recruit participants. Data were collected using a semi‐structured interview guide. Saturation of data was reached after the eighth participant was interviewed. The interviews were audio‐recorded and lasted between 30-70 min, and the data were analysed concurrently with data collection using content analysis. Three major themes emerged. Results Participants experienced hair loss, changes in skin and nail pigmentation and social isolation. The study further revealed that inadequate access to information from healthcare providers and lack of resources coupled with financial constraints were among the major challenges participants faced. However, varied supports from significant others were of much help which enabled participants to go through their chemotherapy successfully.